Subjective assessment of audio watermarked quran - Adamu, Abubakar Ibrahim; Zeki, Akram M. (Universiti Sains Islam Malaysia (USIM), 2014)
Audio Quran is now accessible in many websites free of charge. People can listen online or download any verse or the complete Quran verses. The genuineness of the sound content in those online audio Quran by principle should remain intact. Any intentional or non-intentional alteration to the content creates a big problem. There are reports on circulating fake sound output of online audio Quran intended to alter with the original message the Quran delivers and eventually create confusion. We use different audio watermarking technique for the protection of the originality of online audio Quran content. In this case a watermark is embedded into the bit-stream of audio Quran. This will help in verifying any suspicious fake audio Quran in internet. Unfortunately, there is a concern regarding this method, because the watermark may alter with the contents of the Quran sound, this might create more harm than good. As a result this paper aimed at watermarking some selected short surah of audio Quran and investigates the watermarked conditions by extensive subjective listening test. Furthermore, a model suitable for watermarking and verifying authentic audio Quran is proposed. The result is the combination of good watermarking technique suitable for protecting the integrity of audio Quran and a model for verifying contains of the audio Quran.